Cognitive enhancement. Issue 1 (22nd October 2013) - Farah, Martha J.; Smith, M. Elizabeth; Ilieva, Irena; Hamilton, Roy H.
<x xml:space="preserve">Abstract</x> Cognitive enhancement refers to the improvement of cognitive ability in normal healthy individuals. In this article, we focus on the use of pharmaceutical agents and brain stimulation for cognitive enhancement, reviewing the most common methods of pharmacologic and electronic cognitive enhancement, and the mechanisms by which they are believed to work, the effectiveness of these methods and their prevalence. We note the many gaps in our knowledge of these matters, including open questions about the size, reliability and nature of the enhancing effects, and we conclude with recommendations for further research. WIREs Cogn Sci 2014, 5:95–103. doi: 10.1002/wcs.1250 Conflict of interest: The authors have declared no conflicts of interest for this article. For further resources related to this article, please visit the WIREs website.